A bibliometric analysis of select information science print and electronic journals in the 1990s - Wallace Koehler; et al. (Information Research: An International Electronic Journal)
This paper examines three e-journals and one paper journal begun in the 1990s within the information science genre. In addition, these journals are compared to what is perhaps the leading information science journal,one that has been published continuously for fifty years.  The journals we examine are CyberMetrics, Information Research, the Journal of Internet Cataloging, Libres, and the Journal of the American Society for Information Science. We find that there are a number of important differences among the journals. These include frequency of publication, publication size, number of authors, and the funding status of articles. We also find differences among journals for distributions of authors by gender and corporate authors by region. Some of the regional differences can be explained by journal maturation -- the more mature the journal the greater the dispersion. We also find that women are more likely to publish in the newer journals than in JASIS.  The fact that a journal is or is not an e-journal does not appear to affect its presence or "behaviour" as an information science journal.